Violation towards Charismatic Domination in Atiq Rahimi’s The Patience Stone - Sumarsono, Irwan; Fanani, Abu (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
This study is a qualitative research that was conducted to analyze the violation towards charismatic domination by a woman as reflected in Atiq Rahimi’s The Patience Stone. The writers use the sociological approach to analyze the charismatic domination. The researcher uses the descriptive method in analyzing the study. The researcher also uses the theory of domination of Weber. The main source of this study is the novel The Patience Stone, while the supporting data are taken from books, journals, and from the internet. Using the theory of domination referring to the Mullah and the husband, the researcher finds that the woman as a wife dares to violate the religious teaching as she feels lonely, tortured, as well as despaired by those two charismatic domination.